AB1030 Phospho-calcium metabolism in patients with hip fracture. (23rd January 2014) - Aparicio, M.; Martin-Esteve, I.; Estrada, P.; Montero, A.; Coscujuela, A.; Gomez-Vaquero, C.
Abstract : Background: In Spanish population, there is a high prevalence of hypovitaminosis D which is more severe in elderly patients and, above all, in patients with hip fracture. Objectives: Study the analytical parameters of phospho-calcium metabolism in patients with hip fracture, with special emphasis on the serum concentration of calcidiol and on response to supplements of calcium and vitamin D. Methods: Prospective cross-sectional study including individuals admitted for hip fracture to a university hospital in the period between March 1, 2009 and December 31, 2010. Pathological or secondary to high impact trauma fractures, and patients with a glomerular filtrate <30 ml/min were excluded (n: 101).All patients were interviewed and variables were systematically introduced into a database. Socio-demographic, clinical and analytical data related to the status of the patient prior to fracture, complications arising during admission and follow-up were collected at 3 months and a year. The following analytical parameters of phospho-calcium metabolism were identified in peripheral blood: corrected calcium, phosphate, total alkaline phosphatase (FFAA), calcidiol, and parathormone (PTH). Seventy-eight (24%) patients were receiving supplements of calcium and vitamin D. Deficiency of vitamin D was defined as the serum concentration of calcidiol <25 nM/L andinsufficiencyas <50 nM/L. Results: We included 324 patients (83±8 years, 71% women). The analytical parameters are shown in the table below. 58% of patients had vitamin D deficiency. The monthly distribution of the average concentrations of calcidiol showed a statistically significant increase in the summer months. Patients receiving calcium and vitamin D supplements had a higher mean serum concentration of calcidiol (47.6±43.4 nM/L vs 25.2±11.2 nM/L; p<0.001), a lower vitamin D deficiency (24% vs. 60%; p<0.001) and insufficiency (71% vs 96%; p<0.001) than those who did not receive them. The rest of analytical parameters were not different between the two groups. Conclusions: In hospitalized patients with hip fracture, there is a high prevalence of hypovitaminosis D which did not achieve a satisfactory decrease in the subgroup that received vitamin D supplements. Disclosure of Interest: None Declared